2002
DOI: 10.1046/j.1365-2885.2002.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of transdermal methimazole in a pluronic lecithin organogel (PLO) in healthy cats

Abstract: The antithyroid drug methimazole is widely used for the medical management of feline hyperthyroidism. Recently, custom veterinary pharmacies have offered methimazole in a transdermal gel containing pluronic and lecithin (PLO), with anecdotal evidence of efficacy. The purpose of this study was to determine the bioavailability, relative to i.v. and oral routes of administration, of transdermal methimazole in a PLO gel in cats. Six healthy adult cats were assigned to receive 5 mg of methimazole by the i.v., oral,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 19 publications
5
64
0
Order By: Relevance
“…A HPLC-UV protocol was established, based on a method described previously (Hoffman et al, 2002), for the determination of plasma concentrations of MMZ. An Agilent model 1100 (Agilent Technologies, Santa Clara, CA) HPLC system with a diode array UV detector was used.…”
Section: Methodsmentioning
confidence: 99%
“…A HPLC-UV protocol was established, based on a method described previously (Hoffman et al, 2002), for the determination of plasma concentrations of MMZ. An Agilent model 1100 (Agilent Technologies, Santa Clara, CA) HPLC system with a diode array UV detector was used.…”
Section: Methodsmentioning
confidence: 99%
“…The pluronic lecithin organogel was prepared (Hoffman et al, 2002) at room temperature by first taking the specified amount of soybean lecithin in isopropyl palmitate (IPP) used as dispersing, emulsifying, and stabilizing agent (Willimann & Luisi, 1991) and then keeping the mixture overnight for complete dissolution of lecithin. In this sorbic acid was added as preservative.…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…Some in vivo studies have revealed the ability of PLO gels to be excellent drug carriers with penetration enhancement ability. Significant drug penetration into the systemic circulation was observed on repeated topical application of methimazole to the inner pinna of healthy cats suffering from hyperthyroidism, which was not observed after a single application (67). This was assumed to be a consequence of lowered resistance to the drug penetration caused by the exfoliation of stratum corneum produced by the lecithin component in the gel (62).…”
Section: Plo Gels For Transdermal Drug Deliverymentioning
confidence: 99%